2000
DOI: 10.1021/jf000422s
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Quantitative Determination, and Antioxidative Activities of Chlorogenic Acid Isomers in Prune (Prunus domestica L.)

Abstract: Neochlorogenic acid (3-CQA) and cryptochlorogenic acid (4-CQA), isolated from prune (Prunus domestica L.), were identified by NMR and MS analyses. In addition, the quantity of chlorogenic acid isomers in prune were measured by HPLC. These isomers, 3-CQA, 4-CQA, and chlorogenic acid (5-CQA), were contained in the ratio 78.7:18. 4:3.9, respectively. 4-CQA was identified and quantified in prune for the first time, and relatively high amounts of this isomer were characteristic. Antioxidative activities of the chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
235
1
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(265 citation statements)
references
References 16 publications
21
235
1
8
Order By: Relevance
“…The main groups of polyphenols were proanthocyanidins, hydroxycinamic acids, quercetin glycosides and anthocyanins. The same groups of polyphenols were previously found in plum fruits (Balasundram et al 2006;Chun et al 2003;Dimitrios 2006;Nakatani et al 2000;Stacewicz-Sapuntzakis et al 2001;Tomas-Barberan et al 2001;Walkowiak-Tomczak et al 2008;Cevallos-Casals et al 2006;Donovan et al 1998;Łoś et al 2000;Usenik et al 2009;Kim et al 2003a, b).…”
Section: Characterization Of Polyphenols Composition In Plum Pomacessupporting
confidence: 77%
See 1 more Smart Citation
“…The main groups of polyphenols were proanthocyanidins, hydroxycinamic acids, quercetin glycosides and anthocyanins. The same groups of polyphenols were previously found in plum fruits (Balasundram et al 2006;Chun et al 2003;Dimitrios 2006;Nakatani et al 2000;Stacewicz-Sapuntzakis et al 2001;Tomas-Barberan et al 2001;Walkowiak-Tomczak et al 2008;Cevallos-Casals et al 2006;Donovan et al 1998;Łoś et al 2000;Usenik et al 2009;Kim et al 2003a, b).…”
Section: Characterization Of Polyphenols Composition In Plum Pomacessupporting
confidence: 77%
“…Malic and citric are the main organic acids (Walkowiak-Tomczak et al 2007;Usenik et al 2009). Plums are a rich source of polyphenols, there are most of all flavonols, and caffeic acid derivatives: neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid as well as anthocyans and flavonols (Balasundram et al 2006;Chun et al 2003;Dimitrios 2006;Nakatani et al 2000;Stacewicz-Sapuntzakis et al 2001;Tomas-Barberan et al 2001;Walkowiak-Tomczak et al 2008). The content of anthocyans depends on cultivar and is caused by size differences of fruits and the ratio of peel mass to flesh mass.…”
Section: Introductionmentioning
confidence: 99%
“…The plum fruit is a good source of vitamins, minerals, fiber and enzymes that are good for the digestive system and positively associated with nutrient intake, improves anthropometric measurements; the prune is a useful antistresser (Hiramoto, 2008) and reduces risk of hypertension (Beals and Fulgoni, 2005;Ahmed et al, 2010a). Besides various sugars, acids, pectins, tannins and enzymes, European plum fruits also contain several important secondary metabolites such as flavonoids and phenolic acids (Tomas-Barberan et al, 2001;Gil et al, 2002;Walkowiak-Tomczak et al, 2008;Slimestad et al, 2009), with a strong antioxidant capacity (Kahkonen et al, 1999;Nakatani et al, 2000;Vinson et al, 2001;Kayano et al, 2002Kayano et al, , 2003Kayano et al, , 2004Kikuzaki et al, 2004;Kimura et al, 2008;Rop et al, 2009;Dhingra et al, 2014). Ascorbic acid is another antioxidant present in plum fruit, essential for higher primates and a small number of other species (Gil et al, 2002).…”
Section: In Sarpagandha (Rauvolfia Serpentina)mentioning
confidence: 99%
“…CGA and CA showed ability to inhibit N-nitrosation of an aromatic compound (2,3-diaminonaphthalene) via scavenging nitrogen sesquioxide (N 2 O 3 ) faster than most of other antioxidants (Kono et al, 1997). Nakatani et al (2000) demonstrated that some CGA isomers (3-, 4-and 5-CQA) isolated from prune showed antioxidant activity, such as elimination of superoxide radicals and inhibitory effect against oxidation of methyl linoleate. Additionally, Natella et al (2002) evaluated the antioxidant capacity of coffee and black tea and showed that coffee has a higher antioxidant capacity than tea in hydrophilic medium.…”
Section: Antioxidant Activity Of Hydroxycinnamic Acidsmentioning
confidence: 99%